Karyotype of Incilius valliceps (Anura: Bufonidae) and finding of sex chromosomes (ZW/ZZ) revealed in phenotypic male - Hernández-Guzmán, Javier; Arias-Rodriguez, Lenin (Ecosistemas y Recursos Agropecuarios, 2024)
The coastal toad Incilius valliceps, which have been little studied and understood from several biological and ecological perspectives. The aim of the present study was to describe the typical karyotype in mitosis of I. valliceps from two females and five adult males from two localities of Tabasco state, Mexico. All specimens were subjected to standard cytogenetic treatment. Assembly and karyotype interpretation were based on standard nomenclature. The typical karyotype in mitosis of I. valliceps was integrated by of 2n = 22 chromosomes. However, the presence of two types of karyotypes was observed, one characterized by homogametic males (ZZ) with a chromosome formula of 12msm+8T+2A (NF = 34) and a phenotypic male from La Lima with chromosome formula of genetic female (ZW) with 12msm+8T+1stt+1A (NF = 36). The results indicate sexual setback from the genetic female to a phenotypic male.